2017
DOI: 10.3390/pharmaceutics9040058
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol-Loaded Lipid Nanocarriers: Correlation between In Vitro Occlusion Factor and In Vivo Skin Hydrating Effect

Abstract: Lipid nanocarriers show occlusive properties that may be related to their ability to improve skin hydration. The aim of this work was to evaluate the relationship between in vitro occlusion factor and in vivo skin hydration for three types of lipid nanocarriers: nanoemulsions (NEs), solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs). These lipid nanocarriers were loaded with trans-resveratrol (RSV) and incorporated in gel vehicles. In vitro occlusion factor was in the order SLNs > NLCs >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 32 publications
(37 reference statements)
7
38
0
Order By: Relevance
“…These results are in agreement with the study of Montenegro et al (2017) where it was observed that the gels containing non‐crystalline nanocarriers without solid lipid, e.g. gel with nanoemulsion, showed an occlusion factor significantly higher that the control gel, suggesting that the liquid lipid may contribute to the occlusive properties of the nanocarriers …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in agreement with the study of Montenegro et al (2017) where it was observed that the gels containing non‐crystalline nanocarriers without solid lipid, e.g. gel with nanoemulsion, showed an occlusion factor significantly higher that the control gel, suggesting that the liquid lipid may contribute to the occlusive properties of the nanocarriers …”
Section: Resultssupporting
confidence: 93%
“…An ideal drug delivery system fulfills the objective of maximizing therapeutic effect while minimizing toxicity . Nanoemulsion (NE) is a drug delivery system constituted by nanodroplets with a size between 20 and 200 nm surrounded by surfactant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo topical efficacy under in use conditions of unloaded and IDE-loaded SLN and NLC was assessed according to a protocol previously described [11,12,28]. Fourteen female subjects with average photo-aging were selected (age range: 45-63 years) and experiments were performed according to the rules of the Declaration of Helsinki of 1975, revised in 2008.…”
Section: In Vivo Evaluation Of Gel Formulationsmentioning
confidence: 99%
“…In the last decades, solid lipid nanoparticles (SLNs) have been widely investigated as carriers for topical drug delivery [1][2][3][4][5][6][7]. These colloidal systems, consisting of a solid lipid matrix stabilized by different types of surfactants, have been proposed for skin delivery of various active ingredients including antifungal, anticancer, anti-inflammatory, and antioxidant agents [8][9][10][11][12][13][14][15]. The interest in SLNs arises from their many advantages compared to other colloidal carriers such as possibility of incorporating both hydrophilic and lipophilic drugs, ability to achieve drug-controlled release and targeting, thus improving drug topical bioavailability while reducing systemic side effects [1,4].…”
Section: Introductionmentioning
confidence: 99%